Development, diet and dynamism: longitudinal and cross‐sectional predictors of gut microbial communities in wild baboons. (28th April 2015) - Ren, Tiantian; Grieneisen, Laura E.; Alberts, Susan C.; Archie, Elizabeth A.; Wu, Martin
Summary: Gut bacterial communities play essential roles in host biology, but to date we lack information on the forces that shape gut microbiota between hosts and over time in natural populations. Understanding these forces in wild primates provides a valuable comparative context that enriches scientific perspectives on human gut microbiota. To this end, we tested predictors of gut microbial composition in a well‐studied population of wild baboons. Using cross‐sectional and longitudinal samples collected over 13 years, we found that baboons harbour gut microbiota typical of other omnivorous primates, albeit with an especially high abundance of Bifidobacterium . Similar to previous work in humans and other primates, we found strong effects of both developmental transitions and diet on gut microbial composition. Strikingly, baboon gut microbiota appeared to be highly dynamic such that samples collected from the same individual only a few days apart were as different from each other as samples collected over 10 years apart. Despite the dynamic nature of baboon gut microbiota, we identified a set of core taxa that is common among primates, supporting the hypothesis that microbiota codiversify with their host species. Our analysis identified two tentative enterotypes in adult baboons that differ from those of humans and chimpanzees.